Analisis Secara Kromatografi Gas-Spektrometri Massa Fraksi Etil Asetat Daun Sesewanua (Clerodendrum Squamatum Vahl.) dan Potensi Antidiabetes Secara In Vivo - Wolo, Bona F; Mamuaja, Meiske N; Rumampuk, Rymond J (General Chemistry Journal, 2024)
The sesewanua plant (Clerodendrum Squamatum Vahl.) is a plant that has been used as traditional medicine by the community for generations. In Minahasa sesewanua leaves are used as a medicine for broken bones, fever and to reduce swelling. This study aims to test the antidiabetic potential of male white rats (Rattus novergicus) and analyze the compound content of the ethyl acetate fraction of sesewanua leaves. The isolation stages were carried out using the extraction method, by means of maceration, fractionation and purification carried out using thin layer chromatography and gravity column chromatography. In vivo antidiabetic activity tests were carried out on male white rats (Rattus novergicus) that were injected with streptozotocin. Based on the results obtained, 10 mg of F1 isolate from the ethyl acetate fraction of sesewanua leaves (Clerodendrum squamatum Vahl.), was then analyzed using KG-SM, 6 compounds were obtained with the following compound names; 3-hydroxy-4-methyl-2-pentanone; 3-hydroxyhexadecane-2,15-dione; 3-hydroxy-2 oxoheptadecanal; 9,12,15-Octadecatrienoic, methyl ester; methyl linoleate, and ethyl linoleate. Sesewanua leaf extract (Clerodendrum squamatum Vahl.) was able to reduce blood glucose levels in male white mice induced by HFD and streptozotocin.